Effective services for improving education and employment outcomes for children and alumni of foster care service: correlates and educational and employment outcomes. Issue 2 (5th March 2013) - Barnow, Burt S.; Buck, Amy; O'Brien, Kirk; Pecora, Peter; Ellis, Mei Ling; Steiner, Eric
Abstract Outcomes for youth from foster care have been found to be poor. The education and employment outcomes of youth and alumni of foster care served by transition programmes located in five major US cities were examined. Data were collected by case managers and reported to evaluators quarterly on 1058 youth from foster care for over 2 years. Job preparation, transportation, child care, education support services and life skills were the most common services provided to youth. During the 2‐year study period, 35% of participants obtained employment, 23% obtained a General Education Development or diploma, and 17% enrolled in post‐secondary education. It was found that the longer the youth were enrolled, the more education and employment outcomes they achieved. Further, job preparation and income support services were associated significantly with achieving any positive education or employment outcome. Results indicated that certain services provided over an extended period of time can improve outcomes for youth placed in foster care. For youth to achieve positive outcomes as they transition to adulthood, additional services are necessary. Other implications are discussed.